KUALITAS PELAYANAN ADMINISTRASI MELALUI PROGRAM KIOS E-PAKLADI DI DESA PAREREJO KECAMATAN PURWODADI KABUPATEN PASURUAN JAWA TIMUR - Aminullah; Silpi Riani (Halu Oleo University, 2023)
The research objective was to determine the quality of E-Pak Ladi services in Parerejo Village and what factors influenced these services. This study uses a qualitative descriptive research method. The informants were the Village Head, Village Secretary, E-Pak Ladi Kiosk Operator, and the Community as the beneficiary group. The results showed that the implementation of the E-Pak Ladi Program was based on the theory of service quality from Zeithaml (1990): (1) the implementation of E-Pak Ladi in Parerejo Village fulfilled the Tangibles aspect. (2) the quality of E-Pak Ladi's service in Parerejo Village did not meet the Empathy aspect (3) the quality of E-Pak Ladi's service did not meet the aspect. (4) The quality of E-Pak Ladi's administrative services in Parerejo Village does not yet meet the Responsiveness aspect. (5) The quality of E-Pak Ladi's administrative services in Parerejo Village has not met the Assurance aspect. Supporting factors in improving the quality of E-Pak Ladi services are (1) Support from various parties such as the BPD and other apparatus in the village. (2) Mechanisms or standard procedures from related agencies. (3) Massive communication through the media. (4) Competent human resources in the Parerejo Office. The inhibiting factors for improving the quality of E-Pak Ladi services are: (1) The promises of the Village Government regarding the E-Pak Ladi Program do not match the facts on the ground. (2) The attitude or individual communication patterns of some employees in Parerejo Village are less friendly.